Clinical and seasonal pattern of dengue in a tertiary care hospital of South West India [version 3; peer review: 2 approved] - Robin Poovattil; Darshan BB; Bhaskaran Unnikrishnan; Ramesh Holla; Suryansh Prateek; Ashir Sharma; Basavaprabhu Achappa; Shawna Simmy (F1000Research, 2024)
Background Dengue is an emerging global viral disease with an increase 30-fold in incidence in the past fifty years. In the past decade it was restricted to only few a states of South and Northern India but in the recent past it has affected almost all the states in India. The objective of this study was to assess the clinical profile, trends and outcome of dengue cases. Methods This retrospective record based cross-sectional study was conducted in tertiary hospital, Mangaluru in Southern India. The study population included all dengue positive cases diagnosed either by IgM Capture ELISA or Dengue Non-structural Protein NS1 antigen over a period of five years. Information from pre-recorded case sheets were used for data collection. The data was analyzed using SPSS Version 20. Results from the analysis have been expressed in percentages, means and graphs. Results The study included 401 dengue cases. Most cases were in the age range of 20-40 years with a male to female ratio of 3:2. Overall seropositivity rate was 23.94% with High IgM prevalence. Monthly distribution showed a maximum cases were in the months of June and July and minimum were in January and February. Among the study participants, 91.5% of patients recovered completely and 1.7% of patients had died. 6.8% of patients were discharged against medical advice. Conclusions Dengue continues to be major public health problem in this part of the globe affecting mainly the working age group. Low seropositivity with High IgM prevelance makes dengue an important differential for febrile illness of vague nature and invokes the need for robust public health response to curb the hyper-endemicity.